At Westonci.ca, we make it easy for you to get the answers you need from a community of knowledgeable individuals. Connect with professionals on our platform to receive accurate answers to your questions quickly and efficiently. Explore comprehensive solutions to your questions from a wide range of professionals on our user-friendly platform.
Sagot :
To solve the equation [tex]\(\log x + \log (3x - 13) = \log 10\)[/tex], we can follow these steps:
1. Combine the logarithmic terms on the left side:
We know that the sum of logarithms can be combined into a single logarithm using the property:
[tex]\[ \log a + \log b = \log (a \cdot b) \][/tex]
Therefore, we can rewrite the equation as:
[tex]\[ \log (x \cdot (3x - 13)) = \log 10 \][/tex]
2. Set the arguments of the logarithms equal to each other:
Since the logarithms are equal, we can set the arguments inside the logarithms equal to each other:
[tex]\[ x \cdot (3x - 13) = 10 \][/tex]
3. Simplify and solve the quadratic equation:
Expand the left side:
[tex]\[ 3x^2 - 13x = 10 \][/tex]
Move the constant term to the left side to set the equation to zero:
[tex]\[ 3x^2 - 13x - 10 = 0 \][/tex]
4. Factor the quadratic equation:
We need to factor [tex]\(3x^2 - 13x - 10\)[/tex]. We look for two numbers that multiply to [tex]\(3 \times (-10) = -30\)[/tex] and add to [tex]\(-13\)[/tex].
These numbers are [tex]\(-15\)[/tex] and [tex]\(2\)[/tex]. So, we rewrite the middle term ([tex]\(-13x\)[/tex]) using these numbers:
[tex]\[ 3x^2 - 15x + 2x - 10 = 0 \][/tex]
Now, factor by grouping:
[tex]\[ 3x(x - 5) + 2(x - 5) = 0 \][/tex]
Factor out the common binomial factor [tex]\( (x - 5) \)[/tex]:
[tex]\[ (x - 5)(3x + 2) = 0 \][/tex]
5. Solve for the possible values of [tex]\(x\)[/tex]:
Set each factor equal to zero:
[tex]\[ x - 5 = 0 \quad \text{or} \quad 3x + 2 = 0 \][/tex]
Solve these simple linear equations:
[tex]\[ x = 5 \quad \text{or} \quad x = -\frac{2}{3} \][/tex]
6. Check for the validity of the solutions:
We need to ensure that the solutions are valid by substituting them back into the original logarithmic equation. Both arguments of the logarithms must be positive.
- For [tex]\(x = 5\)[/tex]:
[tex]\[ \log 5 + \log(3 \cdot 5 - 13) = \log 5 + \log 2 \][/tex]
This is valid since both [tex]\(\log 5\)[/tex] and [tex]\(\log 2\)[/tex] are defined.
- For [tex]\(x = -\frac{2}{3}\)[/tex]:
[tex]\[ \log \left(-\frac{2}{3}\right) + \log \left(3 \left(-\frac{2}{3}\right) - 13\right) \][/tex]
The term [tex]\(\log \left(-\frac{2}{3}\right)\)[/tex] is not defined for negative values, so [tex]\(x = -\frac{2}{3}\)[/tex] is not a valid solution.
Therefore, the only valid solution is:
[tex]\[ x = 5 \][/tex]
1. Combine the logarithmic terms on the left side:
We know that the sum of logarithms can be combined into a single logarithm using the property:
[tex]\[ \log a + \log b = \log (a \cdot b) \][/tex]
Therefore, we can rewrite the equation as:
[tex]\[ \log (x \cdot (3x - 13)) = \log 10 \][/tex]
2. Set the arguments of the logarithms equal to each other:
Since the logarithms are equal, we can set the arguments inside the logarithms equal to each other:
[tex]\[ x \cdot (3x - 13) = 10 \][/tex]
3. Simplify and solve the quadratic equation:
Expand the left side:
[tex]\[ 3x^2 - 13x = 10 \][/tex]
Move the constant term to the left side to set the equation to zero:
[tex]\[ 3x^2 - 13x - 10 = 0 \][/tex]
4. Factor the quadratic equation:
We need to factor [tex]\(3x^2 - 13x - 10\)[/tex]. We look for two numbers that multiply to [tex]\(3 \times (-10) = -30\)[/tex] and add to [tex]\(-13\)[/tex].
These numbers are [tex]\(-15\)[/tex] and [tex]\(2\)[/tex]. So, we rewrite the middle term ([tex]\(-13x\)[/tex]) using these numbers:
[tex]\[ 3x^2 - 15x + 2x - 10 = 0 \][/tex]
Now, factor by grouping:
[tex]\[ 3x(x - 5) + 2(x - 5) = 0 \][/tex]
Factor out the common binomial factor [tex]\( (x - 5) \)[/tex]:
[tex]\[ (x - 5)(3x + 2) = 0 \][/tex]
5. Solve for the possible values of [tex]\(x\)[/tex]:
Set each factor equal to zero:
[tex]\[ x - 5 = 0 \quad \text{or} \quad 3x + 2 = 0 \][/tex]
Solve these simple linear equations:
[tex]\[ x = 5 \quad \text{or} \quad x = -\frac{2}{3} \][/tex]
6. Check for the validity of the solutions:
We need to ensure that the solutions are valid by substituting them back into the original logarithmic equation. Both arguments of the logarithms must be positive.
- For [tex]\(x = 5\)[/tex]:
[tex]\[ \log 5 + \log(3 \cdot 5 - 13) = \log 5 + \log 2 \][/tex]
This is valid since both [tex]\(\log 5\)[/tex] and [tex]\(\log 2\)[/tex] are defined.
- For [tex]\(x = -\frac{2}{3}\)[/tex]:
[tex]\[ \log \left(-\frac{2}{3}\right) + \log \left(3 \left(-\frac{2}{3}\right) - 13\right) \][/tex]
The term [tex]\(\log \left(-\frac{2}{3}\right)\)[/tex] is not defined for negative values, so [tex]\(x = -\frac{2}{3}\)[/tex] is not a valid solution.
Therefore, the only valid solution is:
[tex]\[ x = 5 \][/tex]
We appreciate your visit. Hopefully, the answers you found were beneficial. Don't hesitate to come back for more information. We appreciate your time. Please come back anytime for the latest information and answers to your questions. Westonci.ca is here to provide the answers you seek. Return often for more expert solutions.